Gratitude to Gary Gibbs (The sixteenth century journal, 2021)
The article announces that the journal's book reviews editor Gary Gibbs of Roanoke College is no longer going to be editor, and the journal offers its thanks for a job well done. The tasks will be taken by Freddy C. Dominguez of the University of Arkansas' Department of History.